Antibacterial evaluation and molecular properties of pyrazolo[3,4-b] pyridines and thieno[2,3-b]pyridines - Mervat A. Elsherif& (Journal of Applied Pharmaceutical Science, 2021)
A series of pyrazolo[3,4-b]pyridines (6a-h) and thieno[2,3-b]pyridines (8a-h) was synthesized for the evaluation of their in vitro antibacterial activities against four bacteria species (namely Bacillus subtilis, Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa) and compared the result with the standard drug (Tetracycline). The result of the antibacterial evaluation showed that some pyrazolo[3,4-b]pyridines and thieno[2,3-b]pyridines display moderate antibacterial activity against the four bacteria species in this study. Furthermore, the physicochemical, pharmacokinetic, and drug-likeness properties were carried out using SwissADME website. The results of molecular properties show that all the pyrazolopyridines 6a-h and thienopyridines 8a-h showed agreement with the Lipinski and Veber rules. The two pyrazolo[3,4-b]pyridines 6b and 6c are almost in the range of the bioavailability radar pink area. Also, pyrazolo[3,4-b]pyridine derivatives 6a-h show high gastrointestinal absorption, all the derivatives except 6c are nonsubstrates for P-glycoprotein, and most of the derivatives show CYP isoform inhibition. This study could be valuable in the discovery of a new series of drugs.
Keywords: Pyrazolo[3,4-b]pyridine, thieno[2,3-b]pyridine, antibacterial activity, molecular properties, druglikeness.